PENERAPAN DESA PEDULI GAMBUT DI DESA SAWAHAN KECAMATAN CERBON KABUPATEN BARITO KUALA - Achmad Jaelani; Gusti Khairun Ni’mah (Universitas Islam kalimantan MAB, 2019)
Sawahan Village is one of the Transmigration villages in the Cerbon sub-district, BaritoKuala district, South Kalimantan province. This village has a vast expanse of rice fieldsand 90% of the people work as farmers. Sawahan village has an area of 5,950 ha withproductive land of 1,200 ha which is mostly in the form of peatland. The land of thesawahan village is located near the tidal river flow containing low pH with high aciditylevels ranging from 3,5 to 4,5. Land in the area is a type of peat land (black brown), sothat not all plants, livestock and fish can grow / live except plants, fish, livestock thatcan adapt to this condition. Peatlands have their own difficulties in managing them.Some fruit plants and horticulture can live after being adapted to the condition of theland for a long period of time but given a considerable amount of lime to overcome highacidity and disease resistance. With this, many transmigrant farmers have difficulty inhandling the land because some species of plants and fish cannot develop properly. Forthis reason a new breakthrough is needed so that this problem can be overcome andfarmers are able to plant crops, fish and livestock specific to peatlands. Some of theresults of the Uniska Agriculture Faculty trial which tried several plants that wereadaptive to the conditions of peatlands such as Kweni Anjir, Limau Kuit, RambutanAntalagi and Kasturi. In addition to fruit trees, there are also horticultural plants thathave been tried on these peatlands, namely long beans, purple eggplant, bitter melon,tiyung chili (very spicy mini chili). For fish there are fragrant fish (cork) and catfish.Whereas livestock with Alabio ducks are resistant to peatland conditions. In addition tofruit trees, there are also horticulture plants that have been tried on these peatlands,namely long beans, purple eggplant, bitter melon, tiyung chili. The problem in thisactivity is how farmers make efforts in transmigrant areas by selecting mina plants, fishand livestock that are suitable for cultivation on peatlands, how to cultivate mina-plantsand livestock for peatland species to get maximum results and how to pioneer marketingefforts production so that it can really increase the income of transmigrant farmers inSawahan Village, Barito Kuala Regency.